Investigation of students' mathematical mindset in solving mathematical literacy problems - Nailul Himmi; Dian Armanto; Izwita Dewi; Edy Surya; Edi Syahputra (State Islamic University of North Sumatra, 2024)
Mathematical literacy is a crucial competency for university students, yet research indicates that many students struggle to apply it effectively. This study aims to analyze students' mathematical mindsets in addressing mathematical literacy challenges and their implications for mathematics education in higher education. The research employs a descriptive qualitative design, involving three second-semester students selected through purposive sampling. Data collection methods include observation, in-depth interviews, and analysis of mathematical literacy tests, focusing on indicators such as the ability to formulate mathematical situations, apply mathematical concepts and procedures, and interpret mathematical results. Data analysis was conducted through several stages: data reduction, data presentation, drawing conclusions, identifying students' mindsets in solving mathematical problems, and source triangulation. The findings reveal that students' mathematical thinking is influenced by cognitive development, cognitive style, and problem-solving strategies. While some students successfully solve mathematical literacy problems, they still make errors in several concepts and often exhibit carelessness in reading the questions. This research has significant implications for mathematics education in higher education, including the need to emphasize conceptual understanding, balance procedures, and concepts, and utilize visual representations. The development of teaching materials and mathematical literacy questions should be designed to accommodate diverse student mindsets and be grounded in realistic contexts.